Regressions between Sets of Variables - Waugh, Frederick V. (Econometrica, 1942)
PROFESSOR HOTELLING'S PAPER, Relations between Two Sets of Variates,'l should be widely known and his method used by practical statisticians. Yet, few practical statisticians seem to know of the paper, and perhaps those few are inclined to regard it as a mathematical curiosity rather than an important and useful method of analyzing concrete problems. This may be due to two reasons: first, that Hotelling's paper makes use of rather complicated mathematics and does not spell out in detail the methods of numerical computation; and, second, that although the paper applied the methods to two sets of statistical data, the major emphasis is on mathematical theory, and only rather incidental consideration is given to the meaning of the results obtained in actual statistical work. This paper will try to do two things: first, and most important, it will apply these methods to two different kinds of problems in the hope that this will suggest other practical applications; second, it will develop the methods of analysis in somewhat simpler terms, and discuss numerical computation in greater detail than Hotelling's paper.